2012
DOI: 10.1111/j.1467-8659.2012.03188.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four Subjective Methods for Image Quality Assessment

Abstract: To provide a convincing proof that a new method is better than the state of the art, computer graphics projects are often accompanied by user studies, in which a group of observers rank or rate results of several algorithms. Such user studies, known as subjective image quality assessment experiments, can be very time‐consuming and do not guarantee to produce conclusive results. This paper is intended to help design efficient and rigorous quality assessment experiments and emphasise the key aspects of the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(136 citation statements)
references
References 21 publications
1
135
0
Order By: Relevance
“…are important, but do not capture the fine differences in personal opinion. However, paired comparison user-studies, have shown to be well suited for understanding fine opinion differences [8]. Thus, the subjective quality assessments in our work are also based on paired comparisons.…”
Section: B Evaluation Of Resultsmentioning
confidence: 99%
“…are important, but do not capture the fine differences in personal opinion. However, paired comparison user-studies, have shown to be well suited for understanding fine opinion differences [8]. Thus, the subjective quality assessments in our work are also based on paired comparisons.…”
Section: B Evaluation Of Resultsmentioning
confidence: 99%
“…rating, ranking or pair-wise comparisons can impact on precision and length of the experiment. Nevertheless, the results of the different strategies are expected to be correlated [47,139,174].…”
Section: Discussionmentioning
confidence: 99%
“…For each of three candidate rendering methods, eight rendering outputs from different viewpoints for four different scenes, "chess board" and "room" from simulator and "eucalyptus flowers" and " Lego knights" from Stanford real data were generated. These 96 test sequences as a pair of reference and rendering output were presented to each subject with the recommended time pattern and experiment conditions as proposed in [24,55]. The subjects were asked to rate the impairment of the second stimulus in relation to the reference into one of the five-level scales: 5-Imperceptible, 4-Perceptible but not annoying, 3-Slightly annoying, 2-Annoying, and 1-Very annoying.…”
Section: Subjective Assessmentmentioning
confidence: 99%